Revitalization of Islamic Religious Education for the Millennial Generation and Generation Z - Mutia Azzahra Sulaiman; Novi Agustiani; Nusantara Prima Fahan; Reno Antra Yoga Riski; Eva Iryani (Fakultas Agama Islam, 2026)
This study examines the revitalization of Islamic Religious Education in the digital era, particularly in addressing the learning characteristics and religious challenges faced by Generation Z. The rapid development of digital technology has transformed patterns of religious learning, information access, and educational interaction, creating challenges related to digital literacy, religious authority, and contextual learning relevance. This research employed a qualitative approach using a library research design by analyzing recent academic literature, official reports, and scholarly publications related to Islamic education, digital literacy, and Generation Z. The findings reveal several major gaps in Islamic Religious Education, including conventional teacher-centered learning methods, limited integration of contemporary issues, low digital literacy among students, and weak collaboration between schools, families, and communities. In response to these challenges, the study formulates a revitalization model consisting of interactive digital learning, integration of contemporary social issues, strengthening of digital literacy, digital andragogical approaches, and multi-stakeholder collaboration. The novelty of this study lies in its integrative framework combining digital literacy, contextual pedagogy, and religious moderation. This model is expected to support adaptive, relevant, and transformative Islamic Religious Education in the digital era.